Optimization of Water Purification Infrastructures in Supiori Regency - Markus Sawaki; Ira Widyastuti; Duha Awaludin; Bernathius Julison; Mujiati Mujiati (Publikasi Indonesia, 2024)
Clean water is one of the important aspects that must be prioritized in urban planning. The higher the standard of living of the community, the need for clean water will also increase. However, the fulfillment of adequate clean water needs in Supiori Regency is still not optimal. Based on the Minister of Public Works Regulation No. 14/2010, the coverage of drinking water services in Supiori Regency is classified as poor, with a clean water service level of less than 50%. Optimization efforts are needed to optimize and distribute clean water services in Supiori Regency meet the target of clean water services and create a sustainable community life. The research method uses three types of analysis. First, the ratio of clean water services in the settlements of Supiori Regency was analyzed using a calculation method that refers to the standard of clean water needs and availability. Second, the analysis of clean water services was conducted based on community perceptions. Third, this study analyzed the factors that influence clean water services using multiple linear regression. Descriptive analysis was used to identify optimization steps. The results showed that the ratio of clean water services in South Supiori District only reached 30.38%, while in East Supiori District, it was lower, at 19.78%. Based on community perceptions, 93% of the population in South Supiori District and 75% in East Supiori District have not used the Water Supply System. Regression analysis shows that in Supiori Selatan District, factors affecting clean water services include pipe distance, community participation, and number of family members. In East Supiori District, the influencing factors are pipe distance, management, and maintenance of clean water. So, there are optimization efforts that can be done, among others, through mapping services based on regional conditions. For areas that are difficult to reach by SPAM services, the community can utilize the nearest water source to meet their clean water needs independently.